2007
DOI: 10.1021/bm060550a
|View full text |Cite
|
Sign up to set email alerts
|

Reexamining the Egg-Box Model in Calcium−Alginate Gels with X-ray Diffraction

Abstract: The structure of the Ca--alginate junction zones was investigated with X-ray scattering on gels prepared with different methods. Fiber diffraction reveals the popular egg-box model may not be the only possible structure for the junction zones. The (001) reflection, which should be extinguished due to 2/1 helical conformation in the egg-box model, was observed. This was further confirmed by the measurements on Ca--alginate gel beads prepared at different pH where large pieces were formed through a relatively sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
231
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 344 publications
(258 citation statements)
references
References 18 publications
(70 reference statements)
13
231
2
Order By: Relevance
“…14 , the peaks at 2θ=13°and 21.5°are labelled as (110) and (002), respectively (the fibre axis is defined as c-axis). Note that a small shoulder can be observed at 2θ=10.6°in the diffraction pattern in Figure 7b; the origin of this shoulder has been studied in detail in our laboratory and is discussed in another paper 15 . Figure 8 displays X-ray scattering patterns of air-dried alginate samples with different calcium concentrations (the samples were prepared using the dialysis membrane method as explained in the "Materials and Methods").…”
Section: Rehydration Of Alginate-cmc Mixed Gel Beadsmentioning
confidence: 74%
“…14 , the peaks at 2θ=13°and 21.5°are labelled as (110) and (002), respectively (the fibre axis is defined as c-axis). Note that a small shoulder can be observed at 2θ=10.6°in the diffraction pattern in Figure 7b; the origin of this shoulder has been studied in detail in our laboratory and is discussed in another paper 15 . Figure 8 displays X-ray scattering patterns of air-dried alginate samples with different calcium concentrations (the samples were prepared using the dialysis membrane method as explained in the "Materials and Methods").…”
Section: Rehydration Of Alginate-cmc Mixed Gel Beadsmentioning
confidence: 74%
“…Within this picture, the sample is endowed with a given amount of internal stress unavoidably generated during gelation, since gels form in a microscopically heterogeneous configuration. The links resulting from ionic bonds are expected to be reversible in time 44 ; thus, bonds break and reform with time, thereby locally relaxing internal stress. One therefore expects the dynamics to slow down with sample age, because the driving force, viz the internal stress, would decrease progressively.…”
Section: Resultsmentioning
confidence: 99%
“…Donati et al (2005) reported that the frictional force between the calcium-alginate gel network chains increases with increasing length of the alternating mannuronate-guluronate (MG) sequences. Li et al (2007) reported that MG block or short G blocks in calcium-alginate junction zones contribute gel bond stability.…”
Section: Discussionmentioning
confidence: 99%